MARKETING CONCEPT OF THE MANAGEMENT STRATEGIC PLANNING ENTERPRISE ACTIVITY (Economic journal of Lesya Ukrainka Volyn National University, 2020)
In the article describes the main problems formation marketing concept of the management strategic planning enterprise activity. Determined that strategic planning for the enterprise is defined as an organized process of strategic decision-making, the main contents of which is to compare own capabilities with the opportunities and threats of the external environment on the basis of the analysis information and determine its marketing orientation. In addition, in this article formed structure marketing concept of the management strategic planning activity enterprise and the proposed conceptual scheme of the management strategic planning activity enterprise that allows us to make decisions most relevant to the requirements of the dynamic external environment. In the paper also substantiated a methodical approach to setting up a marketing information system basis of effective model building marketing information system of the enterprise.
Keywords: concept, marketing, management, enterprise, strategic planning, enterprise activity.